Effects of different dietary threonine and glycine supplies in broilers fed low-protein diets - Strifler, Patrik; Horváth, Boglárka; Such, Nikoletta; Dublecz, Károly; Pál, László (Frontiers in Veterinary Science, 2024)
The reduction of crude protein (CP) content of broiler diets with balanced amino acid supply can increase the nitrogen utilization efficiency and reduce ammonia emission, the risk of many health problems of birds. Feeding low protein (LP) diets without the impairment of performance traits needs the optimized dietary levels of threonine (Thr), and the nonessential AA glycine (Gly) and serine (Ser). However, the required concentrations and interactions of Thr and Gly+Ser, expressed as Gly equivalent (Glyequi), in LP diets are not fully clear and understood. Therefore, the aim of this study was to investigate the effects of three LP (LP1-3) grower (11-24 days) and finisher (25-35 days) diets with 2% CP reduction compared to the control (C), differing in standardized ileal digestible (SID) Thr to lysine (Lys) ratio (C, LP1, LP3: 63%, LP2: 72%) and Glyequi levels (C: 15.65 g/kg, LP1: 13.74 g/kg, LP2: 13.70 g/kg, LP3: 15.77). The LP treatments did not impair the performance traits of broilers. The LP2 treatment with increased SID Thr-to-Lys ratio (+9.0%) resulted in significantly higher body weight gain and a more advantageous feed conversion ratio in the whole fattening compared to the control treatment with normal CP level (p<0.05). The LP3 treatment containing swine meat meal with similar Glyequi levels compared to the normal CP treatment led to the most advantageous feed conversion ratio in the finisher phase and the highest nitrogen retention efficiency (p<0.05). However, the LP3 treatment with high starch-to-CP ratio negatively influenced the relative carcass weight and the ratio of abdominal fat of broilers (p<0.05).